Marketing Strategy, Competitive Advantage and Marketing Performance : Study of Small Medium- Size Enterprises At Ancol - Maulana Ichsan; Naili Farida; Sari Listyorini (PT. EQUATOR SINAR AKADEMIA, 2022)
This study aims empirical evidence regarding the performance of the marketing effect by the management strategy of the market through the competitive advantages that the statement is sourced from the marketing performance of small medium-size enterprises in the Ancol area as the dependent variable which is influenced by the competitive advantage as an intervening variable and market strategy, as well as research that are new this is the topic under study has never been done by previous researchers. Thus the intent of this research can be called a novelty. The population of this study amounted to 235 of small medium-size enterprises in the region Ancol on the pandemic of Covid-19 by using the formula sample slovin to 70 small medium-size enterprises with a scale of 1 to 10, the Information of the questionnaire to know the interpretation of the market strategies, competitive Advantage and marketing performance. Analysis techniques for data use regression linear with testing intervening.This research is the implementation of the strategy management market mehasilkan a greater influence on competitive advantage. Strategy management market affect the marketing performance through competitive advantage effective in his work as an intervening variable between the management strategies of the market and marketing performance.